Yet Speak We Must. Issue 1 (April 2021) - Soskice, Janet
Abstract : This response to Robin Kirkpatrick's article in this issue of CounterText takes up the theme of what can be said when, through excess, we know that speech fails or will not do. Theologians know this, as did St Paul, and as do poets. Words can be carefully crafted to lead us (manuduction), to involve us, to entice us to play. Dante knew this, as did Aquinas. We can 'fail' in speaking because we have glimpsed what really 'is'.